The use of satellite data in numerical weather prediction. (28th January 2021) - Saunders, Roger
Abstract : This article describes the use of satellite data for NWP. It gives a brief history and then outlines the various different ways that satellites measure the atmosphere. Finally, a summary of the impact in the UK Met Office Unified Model of the different types of satellite and in situ observations is given.